Cannabis Use in First-Episode Psychosis: Associations with Symptom Dimensions and Sociodemographic Factors - Aziz Mohammad (Journal of Pakistan Psychiatric Society, 2026)
Abstract Objective: To determine sociodemographic and clinical predictors of cannabis use among patients with first-episode psychosis (FEP) admitted to a tertiary care psychiatric unit in Pakistan. Methods: This cross-sectional study was conducted at the Psychiatry Unit, Khyber Teaching Hospital, Peshawar, from January 2021 to December 2024. Consecutive inpatients with FEP and no prior antipsychotic exposure were assessed using a structured proforma for sociodemographic and clinical data. Symptom severity was measured with the Positive and Negative Syndrome Scale (PANSS). Binary logistic regression was applied to identify predictors of cannabis use. Results: Among 104 participants (77.9% male; mean age 23.4 ± 8.4 years), cannabis use was reported exclusively among males (28.4%). Unemployment and lower socioeconomic status significantly predicted cannabis use. Being employed (OR = 0.017, 95% CI [0.001–0.367]) or a student (OR = 0.064, 95% CI [0.006–0.693]) was associated with markedly lower odds of cannabis use compared with unemployment. Satisfactory socioeconomic status was also protective (OR = 0.074, 95% CI [0.010–0.522]). Clinically, moderate manic symptoms and higher PANSS activation scores were linked with lower likelihood of cannabis use (p < 0.05). Conclusion: Cannabis use in first-episode psychosis is strongly influenced by social determinants such as occupation and socioeconomic status rather than symptom severity. Culturally informed, gender-sensitive prevention strategies are needed to address substance use risk in psychosis within South Asian contexts.